Civil-military relations in Iraq 2003-7: The Danish experience - Kasper Hoffmann (Danish Institute for International Studies (DIIS), 2009)
This report is concerned with Danish civil-military cooperation in southern Iraq from the deployment of a Danish batallion in 2003 until its withdrawal in 2007. Apart from the general problem of strategic development, the report finds that the operationalization and realistic benchmarking of strategic objectives was a weak point in the civil-military approach. At the international level the operation points to the importance and problems shared by pre-mission civil-military planning and knowledge, as well as the extent to which Denmark is liable to become a purely reactive player, with little or no influence over decision-making. The report makes subsequent recommendations, should the government want to pursue a more comprehensive civil and military approach to international operations.
Keywords: 300; Internationale Truppe; Friedenssicherung; Katastrophenhilfe; Dänemark; Irak